2021
DOI: 10.1016/j.jhep.2020.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Patients with NAFLD do not have severe portal hypertension in the absence of cirrhosis

Abstract: transport kinetics of the conjugated bile acid tracer 11 C-CSar quantified in healthy humans and patients by Positron Emission Tomography (PET).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 2 publications
1
7
0
Order By: Relevance
“…A prospective study of 292 subjects with NAFLD showed that 17% of the subjects who did not have cirrhosis were found to have portal hypertension (HVPG >5 mmHg), in which 0.5% of the subjects had CSPH. 11 Another observational study of 354 subjects with NAFLD also demonstrated similar findings, showing that 12 out of 100 subjects with portal hypertension (only based on clinical manifestation) did not exhibit any advanced fibrosis or cirrhosis. The authors also pointed out that the only significant difference between subjects with and without portal hypertension was the severity of steatosis.…”
Section: Clinically Significant Portal Hypertension In Non-alcoholic Fatty Liver Diseasementioning
confidence: 67%
See 1 more Smart Citation
“…A prospective study of 292 subjects with NAFLD showed that 17% of the subjects who did not have cirrhosis were found to have portal hypertension (HVPG >5 mmHg), in which 0.5% of the subjects had CSPH. 11 Another observational study of 354 subjects with NAFLD also demonstrated similar findings, showing that 12 out of 100 subjects with portal hypertension (only based on clinical manifestation) did not exhibit any advanced fibrosis or cirrhosis. The authors also pointed out that the only significant difference between subjects with and without portal hypertension was the severity of steatosis.…”
Section: Clinically Significant Portal Hypertension In Non-alcoholic Fatty Liver Diseasementioning
confidence: 67%
“…The study also showed that liver stiffness measurement was markedly lower in portal hypertension without cirrhosis, while the ratio between spleen stiffness measurement and liver stiffness measurement was markedly higher in portal hypertension without cirrhosis. 15 In addition, MR-based methods have been well-correlated with a wide range of HVPG measurements (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). A study by Gharib et al 16 demonstrated an independent significant correlation (p=0.015) between HVPG and MRE of the liver, with a median HVPG of 6 mmHg from 23 subjects.…”
Section: Assessment Of Portal Hypertension In Non-alcoholic Fatty Liver Disease Without Cirrhosismentioning
confidence: 97%
“…has not been established. 28,33,34 36 Fibrogenesis in NAFLD, which predominantly occurs at the central area of the liver lobule might be associated with the lower portal pressure and consequent milder splenomegaly compared to that of CLD-C. 20,22 Similarly, the portalpredominant fibrosis in CLD-C accounted for the higher portal pressure and higher ratio of spleen stiffness (SS) to LS of transient elastography in CLD-C patients than in alcohol-related liver disease patients. 37 However, there have been few studies comparing SS and LS between NAFLD patients and CLD-C patients.…”
Section: Discussionmentioning
confidence: 99%
“…reported that splenomegaly grades did not differ between NAFLD and CLD‐C patients with similar liver fibrosis grades, the present study revealed that NAFLD patients had a significantly smaller spleen volume than CLD‐C patients at F3. A recent study regarding hepatic venous pressure gradient measurements of NAFLD patients has reported that clinically significant portal hypertension is rare in NAFLD patients without cirrhosis 36 . Fibrogenesis in NAFLD, which predominantly occurs at the central area of the liver lobule might be associated with the lower portal pressure and consequent milder splenomegaly compared to that of CLD‐C 20,22 .…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, several studies have suggested that PH can be present in the early stages of NASH, when fibrosis is far less advanced or even absent. [2] , [3] , [4] , [5] , [6] , [7] , [8] …”
mentioning
confidence: 99%